Correlation between Gut Microbiome and the Development of Diabetic Kidney Disease - Belinda Mufidah; Muthia Ara Agusti Ayu; Muhammad Al Qarni; Laila Fitria Djaimi; Khairina Azlina; Kevin Tandarto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetic kidney disease (DKD) is a major complication of diabetes mellitus characterized by progressive renal damage driven by metabolic, hemodynamic, and inflammatory mechanisms. Recent studies highlight the gut–kidney axis as a crucial pathway linking intestinal dysbiosis to DKD progression. Therefore, this study aims to investigate the association between gut microbiome alterations and the progression of DKD, as well as to explore potential mechanistic pathways linking microbial dysregulation to renal injury. A comprehensive literature review was conducted using PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar up to August 2025. Eligible studies included English-language human and experimental research evaluating the relationship between gut microbiota composition and DKD pathogenesis. From 241 retrieved articles, 22 studies met inclusion criteria. Most demonstrated significant gut dysbiosis in DKD, with decreased Faecalibacterium prausnitzii, Akkermansia muciniphila, and Butyricicoccus, and increased Escherichia-Shigella, Hungatella, and Enterococcus. Reduced short-chain fatty acid (SCFA) production and accumulation of uremic toxins—such as indoxyl sulfate, p-cresyl sulfate, and phenyl sulfate—were strongly associated with inflammation, fibrosis, and renal decline. The analysis was conducted through qualitative synthesis of study methodologies, microbial profiles, and biochemical markers to identify consistent patterns linking gut dysbiosis to DKD progression. These findings suggest that microbial imbalance and altered metabolite profiles play pivotal roles in DKD development. Interventions targeting the gut microbiota, including probiotics, prebiotics, and dietary fiber, may offer renoprotective benefits through restoration of SCFA-producing bacteria and reduction of uremic toxins. Gut dysbiosis in diabetic kidney disease (DKD) disrupts metabolic and immune balance by reducing beneficial short-chain fatty acid–producing bacteria and increasing pathogenic species, leading to inflammation, proteinuria, and progressive renal decline.